Упростить выражение и найти значение выражения:
(4x-3) 2х - (2x + 1)(3х - 2) - 2х, при х=0,7​

Жилая Жилая    1   08.03.2021 18:03    1

Ответы
Adam1003300 Adam1003300  08.03.2021 18:10

(4x−3)×2x−(2x+1)(3x−2)×2x=8x2−6x−(6x2−4x+3x−2)×2x=8x2−6x−(12x3−8x2+6x2−4x)=8x2−6x−(12x3−2x2−4x)=8x2−6x−12x3+2x2+4x=−12x3+10x2−2x=−2x(6x2−5x+1)

при х=0,7

- 2 \times 0.7(6 \times {0.7}^{2} - 5 \times 0.7 + 1) = - 1.4(2.94 - 3.5 - 1) = - 1.4 \times 0.44 = - 0.616−2×0.7(6×0.72−5×0.7+1)=−1.4(2.94−3.5−1)=−1.4×0.44=−0.616

ПОКАЗАТЬ ОТВЕТЫ